Determining Factors of Village Fund Fraud: Integration of Pentagon Fraud and Morality inStudy of Village Government in the Special Region of Yogyakarta Province - Wahyu Manuhara Putra; Ramonalisa Ramonalisa (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2026)
Fraud in the management of village funds remains a critical issue in public financial governance in Indonesia, along with the increasing budget allocation and complexity of its management. This study aims to analyze the influence of financial pressure, ineffective monitoring, competence, rationalization, village apparatus position, and morality on village fund fraud. This research employs a quantitative approach using primary data collected through questionnaires distributed to 180 village officials in the Special Region of Yogyakarta. The analysis technique used is Structural Equation Modeling based on Partial Least Squares (SEM-PLS) using SmartPLS 3.0. The results show that financial pressure, rationalization, and village apparatus position have a significant positive effect on village fund fraud, while morality has a significant negative effect. Meanwhile, ineffective monitoring and competence do not have a significant effect on fraud. These findings indicate that individual behavioral factors are more dominant in influencing fraud compared to organizational structural factors. Economic pressure and moral justification are the main driving forces, while morality functions as an effective internal control mechanism. The implications of this study highlight the importance of strengthening integrity and ethical values among village officials as a primary strategy in fraud prevention. In addition, this study contributes theoretically by integrating the fraud pentagon with the morality variable and provides practical contributions for policymakers in improving village financial governance.